Clinical and Laboratory Profiles of 109 Patients diagnosed as Multiple Myeloma in Erbil City. - Yassin, Ahmed K. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Multiple myeloma is characterized by clonal expansion and accumulation of abnormal plasma cells in the bone marrow compartment. This study was conducted to determine the frequency and hematological presentation of multiple myeloma in Nanakaly Hospital in Erbil city. patients and Methods: This descriptive retrospective study was carried out at Nanakaly Hospital over a period of six years from January 2007 to August 2012. A total of 109 patients who were diagnosed with multiple myeloma all were included to analyze the clinical and laboratory profiles. All patients were selected based on preset diagnostic criteria by the WHO. Results: The study showed a male: female ratio of 1:1.1, the mean age of male patients was 57.8 years and for females were 57.9. Backache was the most frequent presentation (41.28%) of the patient then bone pain (33.94%), followed by pallor (10.1%) and bone mass (9.2%). The hematological findings showed anemia in 72% patients. Forty five percent of the bone marrow nucleated cells were plasma cells. Conclusions: Males are affected equally to females by multiple myeloma. Majority of patients present with backache, bone pain and anemia.